Functionalization of Carbon Nanomaterials (e.g. Carbon Nanotubes and Graphene) Using L-Cysteine - Talat, Mahe; Awasthi, Kalpana; Sundar, Shyam; N. Srivastava, Onkarnath (Innovations in Corrosion and Materials Science (Discontinued), 2015)
The present work reports the noncovalent functionalization of carbon nanomaterials e.g. carbon nanotubes (CNTs) and graphene sheets (GS) with amino group using L-cysteine. This method offers a larger number of amino functionalities on the surface of CNTs and GS so that large number of biological and drug molecules can be attached. We have synthesized CNTs by chemical vapor deposition of benzene and ferrocene solution at 850 °C. The GS have been synthesized by thermal exfoliation of chemically prepared graphite oxide by rapid heating at 1050 °C in argon ambient. The as prepared CNTs and GS were functionalized noncovalently with Lcysteine at room temperature. The Ampotericin B effective antibiotic was attached with as-prepared amino functionalized CNTs and GS. The as-prepared amino functionalized and also drug attached CNTs and GS were characterized by scanning electron microscopy (SEM), high resolution transmission electron microscopy (TEM), Fourier transform infrared (FTIR) and Raman spectroscopy.
Keywords: Ampotericin-B